Pendampingan Pembelajaran Menggunakan Media LEGO bagi Anak Usia Dini di TK SATAP SDK Olabolo - Dua Dhiu, Konstantinus (PELITA NUSA TENGGARA, 2025)
The cognitive, motor and social emotional abilities of young children are greatly influenced by the stimulation provided through a learning process that is appropriate to their stage of development. One effective approach is through the use of concrete and fun learning media. LEGO media is an educational game tool that can stimulate children's creativity, logical thinking abilities and fine motor coordination. However, at SATAP SDK Olabolo Kindergarten, the use of this kind of learning media is not optimal, both due to limited resources and lack of teacher training in integrating LEGO media in the learning process. This service activity aims to improve the quality of learning at SATAP SDK Olabolo Kindergarten through intensive assistance to teachers and students in using LEGO media as a learning tool. The methods used in this activity include the initial observation stage, teacher training, direct assistance in the classroom, as well as joint evaluation and reflection. Teacher training focuses on understanding the concept of play-based learning, designing educational activities using LEGO, as well as strategies for facilitating children in directed play activities. Meanwhile, assistance to students is carried out through structured play and learning activities with the guidance of teachers and the service team. The results of the activity show that the use of LEGO media is able to increase children's involvement in learning activities, make it easier for teachers to convey basic concepts such as shapes, colors and patterns, and foster social skills such as cooperation and communication between children. Teachers also show an increase in creativity in designing interesting and meaningful learning. It is hoped that this activity can become a model for developing applicable and sustainable learning in schools, especially in areas with limited access to modern learning media